2021
DOI: 10.1186/s12885-021-07852-2
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of an immune gene-set based prognostic signature for soft tissue sarcoma

Abstract: Background Sarcomas is a group of heterogeneous malignant tumors originated from mesenchymal tissue and different types of sarcomas have disparate outcomes. The present study aims to identify the prognostic value of immune-related genes (IRGs) in sarcoma and establish a prognostic signature based on IRGs. Methods We collected the expression profile and clinical information of 255 soft tissue sarcoma samples from The Cancer Genome Atlas (TCGA) datab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 59 publications
(65 reference statements)
1
8
0
Order By: Relevance
“…25 Several other prognostic immune signatures were then reported. [26][27][28][29][30] To our knowledge, none of them is currently used in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…25 Several other prognostic immune signatures were then reported. [26][27][28][29][30] To our knowledge, none of them is currently used in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the AUC of the IRG risk score for 3-year OS was 0.8, which is outperforming previously published genetic risk scores. 31 These findings indicate that the 14-gene signature may play a critical role in the development and progression of sarcomas and may serve as a prognostic tool. In contrast to previous studies, 32 , 33 , 34 the novel IRG signature proved to be suitable for different sarcoma subtypes.…”
Section: Discussionmentioning
confidence: 86%
“…In STLMS, the OS/RFS of 4GS-high-risk patients was also worse than that of 4GS-low-risk patients ( Supplementary Figure S7a ), while in ULMS, due to the sample size limitation of low-risk patients, there is no statistical difference ( Supplementary Figure S7b ). In addition, Shen et al recently reported a 19-gene prognostic signature for STS [ 24 ]. Compared with this gene signature, the ROC curve showed that our four-gene signature had better performance in both short-term and long-term predictions ( Supplementary Figure S8 ).…”
Section: Discussionmentioning
confidence: 99%